Kinerja Organisasi Dinas Kebudayaan dan Pariwisata Kota Tanjungpinang dalam Pengelolaan Sektor Pariwisata - Erna Eni; Rahma Syafitri (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the organizational performance of the Dinas Kebudayaan dan Pariwisata Kota Tanjungpinang in managing the tourism sector. Tanjungpinang has significant cultural and historical tourism potential; however, tourist visit trends remain fluctuating and unstable. This research employs a descriptive qualitative approach using a case study method and library research as the data collection technique. Data were obtained from official government documents, statistical data from the Central Bureau of Statistics, and relevant previous studies. The analysis is based on the public sector organizational performance theory proposed by Agus Dwiyanto, focusing on two main indicators: productivity and accountability. The findings indicate that administratively the agency has consistently implemented programs and organized cultural events in accordance with planning documents. However, the increase in the number of activities has not consistently contributed to stable growth in tourist visits. In terms of accountability, reporting mechanisms have been implemented, yet substantive transparency and public access to information still require improvement. Therefore, the organizational performance can be categorized as administratively adequate but requires enhancement in program effectiveness and public transparency.